1995
DOI: 10.1159/000239385
|View full text |Cite
|
Sign up to set email alerts
|

Amphotericin B Lipid Complex to Treat Invasive Fungal Infections in Cancer Patients: Report of Efficacy and Safety in 20 Patients

Abstract: 20 patients with proven or suspected fungal infections were treated with the amphotericin B lipid complex (ABLC) with a daily dose of 5 mg/kg for 1-25 days. 6 patients died during the therapy due to fungal infection (3) or underlying disease (3). One patient was not evaluable. 13 patients were cured and improved. ABLC was administered in patients with renal disese avoiding the use of conventional amphotericin B (AmB) because of nephrotoxicity or after failure with AmB. Except for hypokalemia persisting after A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The overall response rate observed in the largest series of cases treated with ABLC published by Walsh et al 15 is consistent with that observed in earlier studies of ABLC [25][26][27] . In this open-label emergency-use study of 556 patients who were refractory to or intolerant of conventional antifungal therapy, the overall response rate (complete and partial) for all 291 evaluable fungal infections was 57.4% (25% complete responses and 32% partial responses).…”
Section: Patients Refractory To or Intolerant Of Previous Antifungal supporting
confidence: 84%
See 1 more Smart Citation
“…The overall response rate observed in the largest series of cases treated with ABLC published by Walsh et al 15 is consistent with that observed in earlier studies of ABLC [25][26][27] . In this open-label emergency-use study of 556 patients who were refractory to or intolerant of conventional antifungal therapy, the overall response rate (complete and partial) for all 291 evaluable fungal infections was 57.4% (25% complete responses and 32% partial responses).…”
Section: Patients Refractory To or Intolerant Of Previous Antifungal supporting
confidence: 84%
“…In clinical trials, ABLC has been shown to be effective in the treatment of immunocompromised patients who are refractory to or intolerant of conventional antifungal therapy, including patients with haematologic malignancies 15,26 , AIDS 15 , bone marrow transplant recipients 15,27 , and solid organ transplant recipients 4 ( Table 1).…”
Section: Patients Refractory To or Intolerant Of Previous Antifungal mentioning
confidence: 99%
“…In animal models, ABLC has been shown to be at least as effective as amphotericin B and substantially less toxic. The drug is indicated for the treatment of severe invasive candidiasis and as second‐line treatment of invasive aspergillosis, cryptococcosis in HIV patients and miscellaneous fungal infections ( Franklin et al , 1997 ; Mehta et al , 1997 ; Oravcocá et al , 1995 ). The drug appears to be cleared rapidly from the serum.…”
Section: Specific Fungal Infections In Bone Marrow Transplant Recipientsmentioning
confidence: 99%